The Centre of Some Skew Polynomial Rings - Amir Kamal Amir (Jurnal ILMU DASAR, 2009)
Let R be any ring with identity 1, σ be an endomorphism and δ be a left σ-derivation. In this paper, we will investigate the centre of some skew polynomial rings in the case when R is a commutative domain and σ is anautomorphism. More precisely, let D be a commutative domain with its quotient field K and σ be an  automorphism of  D. Then, we will show that intersection of  the centre of  skew  polynomial  rings D[x;σ] and D[x;σ,δ].